The Impact of Absenteeism and Islamic Work Ethics on Project Delivery in Public Projectized Organizations in the United Arab Emirates (UAE) - ALKEAIBI, NOORA RASHED (2019)
It has been argued that absenteeism adversely affects employees’ productivity, especially in public sector. As the modern world demands a lot from the employees so the stress levels of the employees were increased and are not able to balance the work and the personal life where the individual is affected physically and psychologically that leads to employee’s absenteeism. This adverse impact might be magnified when it occurs in projectized organizations due to the significance of ‘time’ in fulfilling project objectives. Work ethics might be a feasible solution to reduce this adversity. This study aims to assess of the impact of Islamic work ethics on project managers’ absenteeism and consequently the impact of both variables on project delays in public projectized organizations in the United Arab Emirates (UAE). The study deconstructs the concepts of: Islamic work ethics, absenteeism and project scheduling and relies on literature to develop a quantitative scale the measure those three variables. Through the use of a questionnaire, data was collected from 116 project managers that work for public organizations in the UAE. The collected data was analysed through a series of statistical tests and the results show that there is a negative relationship between Islamic work ethics and absenteeism; and a positive relationship between Islamic work ethics and project completion within scheduled time. The main conclusion of this study enhancing work ethics can be a factor that reduces the absenteeism in turn increases the productivity of the organizations through the on-time completion of projects. Practitioners might work on creating a work environment that foster positive work ethics.